Enterprise Architecture Information System Using the Zachman Framework - Widiadnyana, Putu; Andreyana, Putu Veda (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 4 No 3 (2023): JITTER, Vol.4, No.3 December 2023, 2024)
The use of information technology in companies is mandatory to create advantages for the company. Companies of course expect innovation to be able to compete in the global market. Information system development needs to be carried out to improve good business processes and create effectiveness in customer service. A good framework is an important key in designing to produce a satisfactory enterprise system. The company system description can use a framework that suits your needs, namely the Zachman Framework. The Zachman Framework is used to design production company systems by designing based on the perspectives involved with the system. Using the Zachman Framework in designing company systems will produce designs involving the perspectives of planners, owners, designers, builders, subcontractors and users who will discuss in detail data, function, location, people, time and motivation. The results of system design are in the form of a blueprint or company system framework that can facilitate the production process. Keywords : Enterprise Systems, Enterprise Architecture, Zachman Framework